Letramento acadêmico e digital: práticas de leitura na formação inicial de professores no curso de licenciatura em Língua Inglesa - Silva, Malu Santos da (2025)
With the advancement of digital technologies, there has been a significant increase in interpersonal interaction through a wide variety of digital interfaces and technological platforms. Even prior to the COVID-19 pandemic, digital technologies already played a relevant role in Brazilian society, a reality that was reflected in educational policy documents such as the *Base Nacional Comum Curricular* (BNCC), published in 2018. However, during the pandemic, the development and use of these technologies intensified markedly, becoming essential for maintaining professional, social, and personal activities. In the academic context, this acceleration in the use of digital technologies brought both challenges and opportunities to educational environments, especially regarding digital literacies. Digital literacies go beyond the mere use of technological tools; they encompass complex practices of reading, writing, and interaction shaped by sociocultural contexts. As such, digital literacies demand not only technical skills but also a critical and reflective perspective on the ethical use of technology in education. This study aims to understand how digital literacies contribute to the development of academic literacy among undergraduate students in English Language Teaching (ELT) programs, specifically within the initial teacher education phase of the *Licenciatura* in English Language. The methodological approach adopted was ethnographic in nature and conducted at the *Universidade Federal do Recôncavo da Bahia* (UFRB), on the Amargosa campus — the city in which the researcher resides and from which she holds her undergraduate degree. The study involved 14 participants and employed two types of data collection instruments: a research journal and two questionnaires, used for data triangulation and validation. The rationale for this research lies in the need to understand the influence of digital literacies on the academic literacies of pre-service teachers, especially in the post-pandemic context, as well as the role of reading in the development of English language proficiency. Furthermore, it is important to analyze how pre-service teachers are adapting to the National Guidelines for Initial and Continuing Teacher Education and to policies aimed at the integration of digital technologies in education. Focusing on the training process of future English language teachers and on the development of their reading practices during initial teacher education, the theoretical framework of this study is grounded in research on social literacies (Street, 2007, 2010, 2014; Monte-Mor, 2015; Lea & Street, 2014), which serves as a bridge between academic literacies (Lea & Street, 2014; Kalantzis, Cope & Pinheiro, 2020; Kleiman, 2008) and digital literacies (Dudeney et al., 2016; Coscarelli & Ribeiro, 2005; Ribeiro, 2017, 2020; Levy, 1999; Castells, 1999; Brasil, 2018), as well as studies on reading practices in English as an Additional Language (Leffa, 1996, 2001; Kleiman, 2004; Santaella, 2004, 2014; Koener & Fischer, 2022; Wolf, 2019). Within this context, it became evident that students engage with digital reading in English in heterogeneous and situated ways. Many face barriers such as limited access to highquality instructional materials, unstable internet connectivity, and limited prior familiarity with academic genres in English. Nevertheless, students demonstrate creative appropriation of the digital resources available to them, using these tools to enhance their reading practices, expand their vocabulary, and construct meaning through such intersections. This contextual dimension reinforces the importance of rethinking teacher education in light of contemporary digital demands, recognizing local realities, and promoting inclusive, ethical, and contextually grounded pedagogical practices.